The Grammar of Civil War : A Mexican Case Study, 1857-61 - Fowler, Will, 1966- (Book collections on Project MUSE., 2022)
"Will Fowler examines the grammar of the origin, process, and outcome of civil war, and uses the Mexican 1857-61 Civil War as its principal case study to answer the question of why civil wars are so violent"--